Cu2(OH)PO4, a Near‐Infrared‐Activated Photocatalyst1. Issue 18 (28th March 2013) - Wang, Gang; Huang, Baibiao; Ma, Xiangchao; Wang, Zeyan; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Whangbo, Myung‐Hwan
<x xml:space="preserve">Abstract</x> Crystal power! Libethenite, Cu2(OH)PO4 (see 4–5 μm×1.5 μm image), absorbs strongly in the near‐infrared (NIR) region and is an effective photocatalyst for the decomposition of 2, 4‐dichlorophenol in aqueous solution under NIR irradiation. This NIR activation of the photocatalyst is due to a facile transfer of photogenerated electrons from the trigonal bipyramidal CuII sites to the adjacent octahedral CuII sites.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>